Camp Wood: experience the Flint Hills - Mitchell, Aaron C. (Kansas State University, 2010)
Non-profit organizations seeking to expand their facilities are often met with difficult challenges. Oftentimes, funds are spent maintaining the grounds and facilities of the organization, reserving little or no funds for future expansions, marketing, or emergencies. Instead, these organizations rely on volunteers and donors. Without the guidance of design professionals, expansions may be developed without the direction of a coherent master plan. Circulation networks may need to be reconfigured, and newly constructed buildings may relate poorly to one another and to existing amenities. Camp Wood is one camp facing these dilemmas. Located in the Flint Hills Region of Kansas, between Wichita and Topeka, Camp Wood is a YMCA organization and primarily functions as a summer youth camp for kids ages 7-17. It is the only camp in America located in the tallgrass prairie. The Flint Hills hold many ecological features that can be seen and experienced. There are also several man-made features that could be implemented to save energy, water, and other resources. With a coherent master plan, these natural and man-made features can help teach ecological concepts to campers. A master plan can organize vehicular and pedestrian networks to unify existing facilities and proposed future developments for Camp Wood. The proposed master plan for Camp Wood is largely guided by a set of desired experiences that each camper will experience during their stay at Camp Wood. There are multiple site factors that influence each of these experiences. Once the program is defined and the program needs are determined, the site factors can be used to determine the most suitable location for the desired program elements. An in-depth analysis for each program element guides each program element’s location and design, allowing for each of the desired experiences to be achieved.
Keywords: Master planning; Youth camp; Environmental education; Nature exploration; Self-esteem; Building relationships; Landscape Architecture (0390)